Genomic analysis in Chilean patients with suspected Rett syndrome: keep a broad differential diagnosis - Brito, Florencia; Lagos, Catalina; Cubillos, Jessica; Orellana, Joan; Gajardo, Mallen; Böhme, Daniela; Encina, Gonzalo; Repetto, Gabriela M. (Frontiers in Genetics, 2024)
Introduction: Rett syndrome (RTT, MIM #312750) is a rare genetic disorder that leads to developmental regression and severe disability and is caused by pathogenic variants in the MECP2 gene. The diagnosis of RTT is based on clinical features and, depending on resources and access, on molecular confirmation. There is scarce information on molecular diagnosis from patients in Latin America, mostly due to limited availability and coverage of genomic testing. This pilot study aimed to implement genomic testing and characterize clinical and molecular findings in a group of Chilean patients with a clinical diagnosis of RTT.Methods: Twenty-eight patients with suspected RTT underwent characterization of phenotypic manifestations and molecular testing using Clinical Exome Solution TM CES_V2 by SOPHiA Genetics. Data was analyzed using the commercial bioinformatics platform, SOPHiA DDM TM . A virtual panel of 34 genes, including MECP2 and other genes that are in the differential diagnosis of RTT, was used to prioritize initial analyses, followed by evaluation of the complete exome sequence data.Results: Twelve patients (42.8% of participants) had variants in MECP2, of which 11 (39.2%) were interpreted as pathogenic/likely pathogenic (P/LP), thus confirming the diagnosis of RTT in them. Eight additional patients (28.5%) harbored ten variants in nine other genes. Four of these variants were interpreted as P/LP (14.2%) (GRIN2B, MADD, TRPM3 and ZEB2) resulting in alternative neurodevelopmental diagnoses, and six were considered of uncertain significance. No evident candidate variant was found for eight patients.Discussion: This study allowed to reach a diagnosis in half of the participants. The diagnosis of RTT was confirmed in over a third of them, while others were found to have alternative neurodevelopmental disorders. Further evaluation is needed to identify the cause in those with negative or uncertain results. This information is useful for the patients, families, and clinicians to guide clinical management, even more so since the development of novel therapies for RTT. We also show the feasibility of implementing a step-wide approach to genomic testing in a setting with limited resources.